CFD analysis of base drag reduction using indent modification in suddenly expanded nozzle. (2023) - Rathore, Vaidant; Havaldar, Sanjay N.
Abstract: The total drag is the combination of skin friction, wave and base region drags. With all moving projectiles, rockets, missiles, and launch vehicles, the base pressure at the base or back face is a common concern. Base drag increase in unexpectedly bigger flows due to a sudden expansion of duct size at exhaust. At the duct's outflow, the base pressure is vacuum or sub-atmospheric. To lower the base drag, the vacuum must be increased to near atmospheric pressure to reduce total drag. Base drag is undesirable since it accounts for a large portion of the total drag. The reduction in base drag benefits the space and defense programmers greatly. This is highly responsible to major losses of energy as a result of drag. Out of the different types of drag, base drag, commonly known as wake drag is responsible for increased drag in case of high velocity flow through the nozzles. Henceforth it is imperative to have drag reduction techniques. There are active or passive methods used to reduce base drag. The proper recovery of base pressure can be done by optimum indent geometry and position optimization. In this numerical analysis, different geometric shape and position indents are used on the exhaust duct so at to reduce base drag. It was found from the analysis that the outlet velocity radically alters from the inlet to outlet. Furthermore, the magnitude of velocity was high for the nozzle with a circular indent when compared with other indent geometries in the analysis.